Advances in the study of seismogenic and occurrence mechanism of strong earthquakes by using seismic tomography - Hongli Li; Cai Liu; You Tian; Dong Yan; Zhiqiang Li (地球与行星物理论评, 2022)
In this paper, we review the research progress of domestic and foreign scientists on the relationship between the occurrence of strong earthquakes and crustal heterogeneity, and analyze the advantages and problems of the main research methods. Further analysis shows that the main methods to study the structure of the focal region and seismogenic mechanism of strong earthquakes are as follows: relocating the high-precision focal location of aftershocks by the relative localization method and obtaining the high-resolution seismic wave velocity structure in the focal area by seismic tomography. Different from the mechanism of strong earthquakes in fluid-triggered subduction zones, strong earthquakes occur in or at the boundary of high-velocity anomaly that is easy to accumulate stress, and the weakening of the low-velocity and high-conductivity layer in the middle and lower crust is the main factor that triggers strong earthquakes. Insights into the crustal heterogeneity, seismogenic structure, and seismicity in seismogenic areas can provide important data for earthquake prevention and disaster reduction.